A PHENOMENON OF THE CONFLICT IN EDUCATION FOR SECURITY –AN EXAMPLE OF THE CZECH REPUBLIC (Part 2, continuation) - Janusz Mika (Zeszyty Naukowe Wyższej Szkoły Finansów i Prawa w Bielsku-Białej, 2016)
Security belongs to the basic qualitative standards of citizens’ life in every country. It is a very frequently discussed question involving education for security. The paper presents a concise analysis of the phenomenon related to the conflict of education for security using the example of the Czech Republic.